Managing technology in the hospitality industry - Kasavana, Michael L. (Lansing, Michigan : American Institute and Lodging Educational Institute, 2011)
This textbook provides an overview of the information needs of lodging properties and food service establishments. Readers will learn the basics of purchasing, implementing, maintaining, and managing a variety of technology systems used in hospitality. This edition has been updated with new information on gesture interfacing, multicore processors, PCI DSS with regard to POS systems, and a new section on tablet POS systems.
1.Hospitality technology systems -- 2.Hospitality technology components -- 3.Reservation systems -- 4.Rooms management and guest accounting applications -- 5.Property management system interfaces -- 6.Point-of-sale technology -- 7.Food and beverage management applications -- 8.Sales and catering applications -- 9.Accounting applications -- 10.Information management -- 11.System selection -- 12.System and security maintenance.
Includes index.
Keywords: HOSPITALITY INDUSTRY -- DATA PROCESSING